2018
DOI: 10.3389/fncel.2018.00458
|View full text |Cite
|
Sign up to set email alerts
|

The Interleukin-10 Family of Cytokines and Their Role in the CNS

Abstract: Resident cells of the central nervous system (CNS) play an important role in detecting insults and initiating protective or sometimes detrimental host immunity. At peripheral sites, immune responses follow a biphasic course with the rapid, but transient, production of inflammatory mediators giving way to the delayed release of factors that promote resolution and repair. Within the CNS, it is well known that glial cells contribute to the onset and progression of neuroinflammation, but it is only now becoming ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(115 citation statements)
references
References 158 publications
(254 reference statements)
4
99
0
4
Order By: Relevance
“…Herein, the potent IL-10 anti-inflammatory function [31,93,94] is now validated for chlamydial inflammation by impeding the release of not only cytokines but also chemokines in macrophages, which are congruent with our previous findings [27,41]. Many investigators have reported on IL-10 inhibitory actions in macrophages exposed to protozoans (Leishmania braziliensis and Leishmania chagasi), viruses (Tacaribe Virus), fungal and bacteria (Chlamydia spp., Borrelia burgdorferi, Helicobacter pylori, Staphylococcus aureus, Streptococcus pneumoniae, and Yersinia enterocolitica) [95].…”
Section: Discussionsupporting
confidence: 89%
“…Herein, the potent IL-10 anti-inflammatory function [31,93,94] is now validated for chlamydial inflammation by impeding the release of not only cytokines but also chemokines in macrophages, which are congruent with our previous findings [27,41]. Many investigators have reported on IL-10 inhibitory actions in macrophages exposed to protozoans (Leishmania braziliensis and Leishmania chagasi), viruses (Tacaribe Virus), fungal and bacteria (Chlamydia spp., Borrelia burgdorferi, Helicobacter pylori, Staphylococcus aureus, Streptococcus pneumoniae, and Yersinia enterocolitica) [95].…”
Section: Discussionsupporting
confidence: 89%
“…ATP levels are extremely high in supernatants collected from HIV‐infected patients and IL‐1β concentrations are elevated in the CNS of several CNS disorders including Parkinson's Disease, Alzheimer's Disease, HIV‐associated neurocognitive disorders (Festa, Gutoskey, Graziano, Waterhouse, & Meucci, ; Griffin et al, ; Mogi et al, ), and IL‐10 plays a critical role in limiting neuroinflammation (Burmeister & Marriott, ). Particularly in HIV‐associated neurocognitive disorders the ratio of IL‐1β to IL‐10 is correlated to brain atrophy (Kallianpur, ).…”
Section: Resultsmentioning
confidence: 99%
“…Bonferroni correction was applied to correct for multiple comparisons. Disease, HIV-associated neurocognitive disorders (Festa, Gutoskey, Graziano, Waterhouse, & Meucci, 2015;Griffin et al, 1989;Mogi et al, 1994), and IL-10 plays a critical role in limiting neuroinflammation (Burmeister & Marriott, 2018). Particularly in HIV-associated neurocognitive disorders the ratio of IL-1β to IL-10 is correlated to brain atrophy (Kallianpur, 2014).…”
Section: Experimental Design and Statistical Rationalmentioning
confidence: 99%
“…Thus, both in vivo and in vitro findings indicated that IL-10 downregulated NLRP3, caspase-1, and IL-1β (Figure 1a-c). No significant difference in mRNA levels of NLRP3, caspase-1, and IL-1β between WT and IL-10 −/− microglia-enriched cultures after LPS treatment ( Figure 1c) was due to delayed IL-10 production in WT microglial culture system after LPS treatment [17][18][19][20]. In other words, delayed production of IL-10 in WT microglial cultures made IL-10 miss the window to affect gene transcription and mRNA degradation of these genes, which happened earlier.…”
Section: Il-10 Suppressed Lps-elicited Synthesis Of Nlrp3 Pro-caspasmentioning
confidence: 93%